![-17^0=(-17)^0=1](https://tex.z-dn.net/?f=-17%5E0%3D%28-17%29%5E0%3D1)
![\begin{gathered} (-2)^2\times(-2)^{-5}=(-2)^{2-5} \\ =(-2)^{-3} \\ =\frac{1}{(-2)^3} \\ =\frac{1}{-8} \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20%28-2%29%5E2%5Ctimes%28-2%29%5E%7B-5%7D%3D%28-2%29%5E%7B2-5%7D%20%5C%5C%20%3D%28-2%29%5E%7B-3%7D%20%5C%5C%20%3D%5Cfrac%7B1%7D%7B%28-2%29%5E3%7D%20%5C%5C%20%3D%5Cfrac%7B1%7D%7B-8%7D%20%5Cend%7Bgathered%7D)
Thus, the final answers are 1 and -1/8.
ANSWER If you solve for x you get -4/3 y+5/6 If you solve for y you get -3/4x +5/8.
Step-by-step explanation
and then the second answer is
If you solve for x you get-4/3y +-1/2
If you solve for y you get -3/4x +-1/2
Click on the photo to view full solution
Answer:
do 10 20 20 40 50
Step-by-step explanation:
hope it helps sorry if it does not if not then try 1 2 3 4 5